Estimating crop coefficients for vegetable production and agricultural water management under climate change in sub-humid tropics - Tegegne, Desalegn; Schmitter, Petra S.; Worqlul, A. W.; Lefore, N. (Frontiers Media, 2025)
Understanding current and future crop water demand is crucial for improving agricultural productivity and managing long-term water resources in a changing climate. This study aimed to estimate how the crop water demand will change under different water management practices and climate change scenarios. The field experiment using irrigation decision-making tools was carried out in 2016 and 2017 in Lemo, Ethiopia. Crop and water management data were collected on cabbage and carrot production. The field data were used to estimate the crop coefficient (Kc), and the results were compared with the simulated Kc with the Agricultural Policy Environmental eXtender (APEX) model. Predicted future climate data were used in APEX to evaluate the effect of climate change on future crop water requirements and Kc. The field data analysis indicated that, on average, farmer traditional practice (FTP) treatments used more water than wetting front detector (WFD) treatments. Using the soil water balance method, the average of the two treatments’ Kc values at the initial, mid, and late stages was 0.71, 1.21, and 0.8 for cabbage and 0.69, 1.27, and 0.86 for carrot, respectively. The APEXsimulated Kc has captured the FAO Kc pattern very well with the coefficient of determination (R-square) ranging between 0.5 and 0.74. The APEX simulation and the soil water balance estimated Kc also indicated a strong association with R-square ranging between 0.5 and 0.75 for cabbage and 0.66 and 0.96 for carrot. The projected climate change analysis indicated that the crop water demand is expected to increase in the future due to increasing temperatures. Under climate change scenarios, the growing season potential evapotranspiration will increase by 2.5, 5.1, and 6.0% in 2025, 2055, and 2085 compared to the baseline period, respectively. The simulated Kc indicated a higher coefficient of variation in 2085 with 19% for cabbage and 24% for carrot, while the 2025 period simulated Kc indicated the least coefficient of variation (16 and 21% for cabbage and carrot, respectively). The study shows that current irrigation planning with the available water resources should take into account higher crop water requirements in the region to reduce water scarcity risks.